Towards digital transformation of learning and development business processes and systems in the eThekwini municipality - Ngubane, Millicent Puleng (University of the Witwatersrand, Johannesburg, 2024)
The study focuses on the digital transformation and remodelling of business processes and systems in the municipality’s employee learning and development unit, given the advancement and evolution of technologies that have contributed to redefining the functioning, style and manner of work. The learning and development unit of eThekwini Municipality was selected as the case study to assess how digital transformation can be carried out by the learning and development unit. Further, to assess how employees perceive and respond to a call to transition to digital platforms. The study was devoted to exploring how employees interpret digital transformation in the municipality’s workforce learning and development context. It extends to establishing employees' perceptions of the state of preparedness and factors influencing the operationalisation of digital transformation. Further to assess the framework and digital initiatives already implemented and resources and capabilities secured and needed to support the transformation of learning and development processes. The results of the study discovered that the municipality’s employees understood digital transformation and its impact on business process remodelling for learning and development. Employees were precise about what needed to change and provided the reasons for learning and development to contemplate transformation. The key strategic change is the necessity for a swift transition towards the use of digital technologies to help the municipality achieve its goal of being a smart and learning city. For instance, being a smart city requires the municipality to advance in technology use and increase value proposition resulting in customer satisfaction. The learning and development being mandated and entrusted with employee development it is critical that it leads transformation and ensures employee IT capabilities needed in the digital era. The study made the realisation that the L&D unit is still lagging attributed to a lack of leadership to provide direction, no blueprint to guide the transformation process, insufficient resources and capabilities, increased engagement required with employees, customers, and partners as well as assistance to management change.
A research report submitted in fulfillment of the requirements for the Master of Management, In the Faculty of Faculty of Commerce, Law and Management, Wits School of Governance, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Digital transformation; Learning and development; business processes; SDG-4: Quality education; SDG-8: Decent work and economic growth